Effects ESG, Profitability, Institutional Ownership, and Firm Size Effects on Financial Distress: Firm Life Cycle Moderation - Cutserly Utari; Rina Br. Bukit; Yeni Absah (Harmoni Economics: International Journal of Economics and Accounting, 2026)
This study aims to analyze the effects of Environmental, Social, and Governance (ESG), profitability, institutional ownership, and firm size on financial distress, with the firm life cycle serving as a moderating variable, among consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using panel data regression analysis with EViews 12 software and Moderated Regression Analysis (MRA). The sample consists of 11 companies selected through purposive sampling, resulting in a total of 44 observations. Financial distress is examined as an important indicator of a company’s financial health and sustainability, while the selected independent variables are expected to explain variations in financial performance and risk. The findings reveal that profitability has a positive and significant effect on financial distress, indicating that changes in profitability are associated with the level of financial distress experienced by the companies. In contrast, ESG, institutional ownership, and firm size do not show a significant effect on financial distress. Furthermore, the moderation analysis demonstrates that the firm life cycle only moderates the relationship between profitability and financial distress. However, it does not moderate the effects of ESG, institutional ownership, or firm size on financial distress. These findings provide empirical evidence regarding the determinants of financial distress and highlight the importance of considering the firm life cycle when evaluating the impact of profitability on corporate financial conditions.